Sodium interception by xylem parenchyma and chloride recirculation in phloem may augment exclusion in the salt tolerant Pistacia genus: context for salinity studies on tree crops. (1st July 2019) - Godfrey, Jessie M; Ferguson, Louise; Sanden, Blake L; Tixier, Aude; Sperling, Or; Grattan, Steve R; Zwieniecki, Maciej A
Abstract: Working in tandem with root exclusion, stems may provide salt-tolerant woody perennials with some additional capacity to restrict sodium (Na) and chloride (Cl) accumulation in leaves. The Pistacia genus, falling at the nexus of salt tolerance and human intervention, provided an ideal set of organisms for studying the influences of both variable root exclusion and potentially variable discontinuities at the bud union on stem processes. In three experiments covering a wide range of salt concentrations (0 to 150 mM NaCl) and tree ages (1, 2 and 10 years) as well as nine rootstock-scion combinations we show that proportional exclusion of both Na and Cl reached up to ~85% efficacy, but efficacy varied by both rootstock and budding treatment. Effective Na exclusion was augmented by significant retrieval of Na from the xylem sap, as evidenced by declines in the Na concentrations of both sap and wood tissue along the transpiration stream. However, while we observed little to no differences between the concentrations of the two ions in leaves, analogous declines in sap concentrations of Cl were not observed. We conclude that some parallel but separate mechanism must be acting on Cl to provide leaf protection from toxicity specific to this ion and suggest that this mechanism is recirculation of Cl in the phloem. The presented findings underline the importance of holistic assessments of salt tolerance in woody perennials. In particular, greater emphasis might be placed on the dynamics of salt sequestration in the significant storage volumes offered by the stems of woody perennials and on the potential for phloem discontinuity introduced with a bud/graft union.